A concise and regioselective synthesis of 6-bromo-5-methoxy-1H-indole-3-carboxylic acid and its derivatives: Strategic development toward core moiety of Herdmanine D. Issue 5 (3rd March 2020) - Sharma, Pankaj; Sharma, Nutan; Kashyap, Gunjan; Bhagat, Sunita
Abstract: A concise, regioselective and highly efficient strategy for the construction of 6-bromo-5-methoxy-1 H -indole-3-carboxylic acid has been developed through trifluoroacetylated indole driven hydrolysis. The developed protocol has the advantage of selectively directing bromine substituent on one position. The formation of this regioselective product was confirmed by 1 HNMR data. The attractive feature of this new strategy is that the 6-bromo-5-methoxy- 1 H-indole-3-carboxylic acid is an important scaffold of anti-inflammatory naturally occurring compound Herdmanine D. Furthermore, bromo indoles bearing carboxylic acid group were further functionalized in amide derivatives by using various aromatic/aliphatic amines through ultrasonic irradiation. Graphical Abstract: